2020
DOI: 10.1186/s13058-019-1243-8
|View full text |Cite|
|
Sign up to set email alerts
|

A window-of-opportunity trial of the CXCR1/2 inhibitor reparixin in operable HER-2-negative breast cancer

Abstract: Background: Cancer stem cells (CSCs) are purported to be responsible for tumor initiation, treatment resistance, disease recurrence, and metastasis. CXCR1, one of the receptors for CXCL8, was identified on breast cancer (BC) CSCs. Reparixin, an investigational allosteric inhibitor of CXCR1, reduced the CSC content of human BC xenograft in mice. Methods: In this multicenter, single-arm trial, women with HER-2-negative operable BC received reparixin oral tablets 1000 mg three times daily for 21 days before surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…In preclinical models of TNBC, IL-8 inhibition was shown to revert the mesenchymal phenotype, decrease MDSCs in the TME and enhance tumor cell killing by T and NK cells ( 202 ), providing the rational for combining IL-8 inhibitors with immunotherapy or chemotherapy. Reparixin, a small molecule inhibitor of the IL-8 receptors CXCR1 and CXCR2, has been tested in clinical trials (NCT01861054; NCT01861054) in HER2 − BC patients, reporting a 30% response rate in 27 patients and a decrease in the aldehyde dehydrogenase CSC marker in about 25% of patients ( 203 ). Besides cytokines, molecules involved in the production of the immunosuppressive metabolite adenosine represent promising targets for BC therapy.…”
Section: Strategies To Revert Immune Suppression and Improve Cancer Imentioning
confidence: 99%
“…In preclinical models of TNBC, IL-8 inhibition was shown to revert the mesenchymal phenotype, decrease MDSCs in the TME and enhance tumor cell killing by T and NK cells ( 202 ), providing the rational for combining IL-8 inhibitors with immunotherapy or chemotherapy. Reparixin, a small molecule inhibitor of the IL-8 receptors CXCR1 and CXCR2, has been tested in clinical trials (NCT01861054; NCT01861054) in HER2 − BC patients, reporting a 30% response rate in 27 patients and a decrease in the aldehyde dehydrogenase CSC marker in about 25% of patients ( 203 ). Besides cytokines, molecules involved in the production of the immunosuppressive metabolite adenosine represent promising targets for BC therapy.…”
Section: Strategies To Revert Immune Suppression and Improve Cancer Imentioning
confidence: 99%
“…The authors used Reparixin in elaborate experiments and showed that it has anti-CSCs activity in breast cancer cell lines [ 349 ]. Reparixin has been in several clinical trials with mixed results from such studies ( Table 2 ) [ 350 , 351 ]. Further research involving blocking CXCR1/2 by Singh and colleagues also demonstrated decreased CSC activity in breast cancer [ 352 ].…”
Section: Targeting Cancer Stem Cells In Tumor Microenvironmentmentioning
confidence: 99%
“…It has reached phase 1 clinical trial in multiple myeloma ( Kaufman et al, 2013 ) and systemic lupus erythematosus ( Wallace et al, 2016 ), indicating no severe adverse effects. Apart from CD74, inhibitors against CXCL2 (Reparixin) and CXCL4 (Plerixafor) are also of interest for further investigation ( Steinberg and Silva, 2010 ; Goldstein et al, 2020 ). However, as MIF/CD74 pathway also plays an important role in wound repair by activating pro-survival and proliferative pathways that protects the host during injury ( Farr et al, 2020 ), complete inhibition of CD74 could cause some unpredictable side effects which need precaution.…”
Section: Mif Targeted Treatment Strategiesmentioning
confidence: 99%